Sustainable development in the process industries : cases and impact - Harmsen, Jan, 1950-; Powell, Joseph B., 1956- (Wiley, 2010)
Because of the growing interest among petroleum, recycling, and other industries, sustainability is central to chemical engineers and students. Sustainable Development in the Process Industry not only explores but also demonstrates practical solutions for using sustainable technologies, focusing on three major points: people, prosperity, and planet. Rather than presenting theories, the text provides examples and cases studies ranging from the petroleum industry to the water processing industry. With a collection of international authors, the text is suitable for any chemical engineer or student interested in achieving a more sustainable world.